2022
DOI: 10.18778/8220-819-1
|View full text |Cite
|
Sign up to set email alerts
|

Organizacje wobec wyzwań zrównoważonego rozwoju – wybrane aspekty

Abstract: Monografia wpisuje się w nurt rozważań na temat aktualnych procesów i zjawisk związanych z wdrażaniem w organizacjach idei zrównoważonego rozwoju. W prezentowanej książce autorzy podkreślają, iż w kontekście zrównoważonego rozwoju organizacji dochodzi na gruncie naukowym do ścierania się licznych poglądów oraz powstawania nowych teorii. Stąd też książkę należy traktować nie jako wyczerpującą swoją treścią analizę omawianych aspektów, a jako przyczynek do dyskusji dotyczącej problematyki zmian we współczesnych … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…Based on the analysis carried out, it can be concluded that when discussing the issue of GJs, an important emphasis is placed on the “education” keyword, which is located close to “employment” in a green cluster in Figure 2 . To the “education” keyword there are other related terms such as knowledge, skills, attitudes [ 83 , 84 ], and pro-environmental behavior of employees researched deeply in Green Humans Resources [ 29 , 85 ]. These are the elements of complex business activities that indicate whether or not an employee employed at a given green job will contribute to minimizing the negative impact of a given economic entity on the environment [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the analysis carried out, it can be concluded that when discussing the issue of GJs, an important emphasis is placed on the “education” keyword, which is located close to “employment” in a green cluster in Figure 2 . To the “education” keyword there are other related terms such as knowledge, skills, attitudes [ 83 , 84 ], and pro-environmental behavior of employees researched deeply in Green Humans Resources [ 29 , 85 ]. These are the elements of complex business activities that indicate whether or not an employee employed at a given green job will contribute to minimizing the negative impact of a given economic entity on the environment [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the “education” keyword there are other related terms such as knowledge, skills, attitudes [ 83 , 84 ], and pro-environmental behavior of employees researched deeply in Green Humans Resources [ 29 , 85 ]. These are the elements of complex business activities that indicate whether or not an employee employed at a given green job will contribute to minimizing the negative impact of a given economic entity on the environment [ 84 ]. This area was indicated also automatically by the bibliometric software as the first and most numerous cluster in both analyses of Queries 4 and 5.…”
Section: Discussionmentioning
confidence: 99%
“…Zrównoważony rozwój zajmuje istotne miejsce we współczesnym dyskursie naukowym ukierunkowanym na wyznaczenie przyszłego docelowego kierunku rozwoju gospodarki (Kozar, Oleksiak, 2022). Koncepcja ta stanowi obszar zainteresowań wielu badaczy przedmiotu (Ruggerio, 2021;Ozili, 2022).…”
Section: Wprowadzenieunclassified
“…Bez względu na obszar tematyczny, w jakim poruszana jest koncepcja zrównoważonego rozwoju, u jej podstaw leżą dwie powiązane ściśle ze sobą i uzupełniające się nawzajem kwestie. Z jednej strony wskazuje się, iż jest to dążenie do takiego rozwoju gospodarczego, który zapewniałby tożsamy rozwój przyszłym pokoleniom, jak to ma miejsce w stosunku do obecnych pokoleń (Mäler, 2008;Kozar, Oleksiak, 2022). Następuje więc tutaj odwołanie do sprawiedliwości międzypokoleniowej (Golub i in., 2013;Spijkers, 2018;Zikic, 2018) oraz podkreślenie, iż przyszłe pokolenia mają takie same prawa w zakresie swojego rozwoju, jak obecne pokolenia (Zheng, Dai, 2012).…”
Section: Wprowadzenieunclassified
“…Współcześnie kapitał ludzki uznawany jest za jeden z kluczowych zasobów i wartości organizacji, a skuteczne zarządzanie nim może stanowić jedno z wyzwań zrównoważonego rozwoju. Jednym z elementów zrównoważonego zarządzania zasobami ludzkimi, obok planowania zatrudnienia, rekrutacji i selekcji czy oceny pracowniczej, jest obszar motywowania pracowników (Kozar, Oleksiak, 2022). Tematyka czynników wpływających na poziom motywacji zatrudnionych jest również szeroko omawiana w literaturze naukowej z obszaru zarządzania zasobami ludzkimi.…”
Section: Wprowadzenieunclassified